A rare case of hepatolenticular degeneration with double panda sign on imaging - Dadu, Fahad Mohammedamin; Kumar, Sathish; Kumar, Ram; Kumar, Magesh (International Journal of Advances in Medicine, 2022)
Wilson’s disease is an inborn error of copper metabolism that is characterized by deficiency of ceruloplasmin, the serum transport protein for copper. Copper is collected in the liver, and after hepatic binding sites are saturated, it is released. Systemic disease then develops and there is abnormal accumulation of copper in the brain, particularly in the putamen and globus pallidus. Presenting this case of a 32-year-old male patient who presented with peculiar features for Wilson’s disease.